Pengaruh Media Flashcard Terhadap Minat dan Kemampuan Membaca Bahasa Inggris Siswa - Noer, Muhammad Zarkasih; Kusmiyati, Kusmiyati; Tobing, Viktor Maruli L. Tua (Jurnal Ilmiah Wahana Pendidikan, 2024)
English education in elementary schools is an additional subject, but has an important role in providing basic education in English. Therefore, English language education in elementary schools should not be considered trivial compared to other compulsory subjects because it will have an impact on students' readiness to study English at secondary school level. The basic ability in learning a language is the ability to read. Students experience various obstacles in understanding English reading in elementary school because English has different reading characteristics from Indonesian. Flashcard media is a card media that helps remember and review learning material such as: definitions or terms, symbols, foreign language spellings, formulas, and so on. By using the right media, students will easily remember and understand English reading texts and this will be able to increase students' interest in learning. The research objectives were to: 1) determine the influence of flashcard media on the interest of class V students at UPTD SDN Mlajah 1 Bangkalan, 2) determine the influence of flashcard media on the English reading ability of class V students at UPTD SDN Mlajah 1 Bangkalan, and 3) determine the effect of flashcard media on Interest and English Reading Ability of Class V Students of UPTD SDN Mlajah 1 Bangkalan. This research is quantitative research using questionnaire instruments and test questions. The research data was analyzed using paired sample t test and MANOVA analysis techniques to produce research conclusions including: 1) There is an influence of flashcard media on the interest of class V students at UPTD SDN Mlajah 1 Bangkalan, 2) there is an influence of flashcard media on the English reading ability of class V students. UPTD SDN Mlajah 1 Bangkalan, and 3) There is an influence of Flashcard Media on the English Reading Interest and Ability of Class V Students of UPTD SDN Mlajah 1 Bangkalan.